Interesting new ammonites from the Upper Jurassic of Argentina and their correlation potential: New possibilities for global correlations at the base of the Upper Tithonian by ammonites, calpionellids and other fossil groups - Zeiss, Arnold (2008)
Two ammonites from the Vaca Muerta Formation cropping out at the southern slope of Cerro Lotena (Neuquén Basin, Argentina) are described for the first time: 1) Simplisphinctes (Lotenia) neuquenensis, n. subgen., n. sp., and 2) a completely preserved adult microconch of Windhauseniceras internispinosum (Krantz). The beds which contained the ammonites belong to the lowermost Upper Tithonian Windhauseniceras internispinosum Zone. These new findings, especially Simplisphinctes (Lotenia) neuquenensis, allow providing further arguments for the correlation between the W. internispinosum Zone of the Andean Jurassic Province and the Simplisphinctes [abnormisc] Zone of the Mediterranean Jurassic Province. In this context it should be emphasized that at the base of the Upper Tithonian global biostratigraphical correlations are possible by various other guide fossil groups, such as calpionellids (chitinoidellids). For example, in the western part of the Mediterranean area, the Simplisphinctes Zone can be correlated with the Chitinoidella boneti Subzone of the Chitinoidella Zone. This Subzone can be identified also in Cuba in the S. (Paralytohoplites) caribbeanus Zone allowing an improvement of age calibration of this zone. This Simplisphinctes Zone belongs to the lowermost Upper Tithonian and not to the upper Middle Tithonian as hitherto assumed. This is in accordance with a morphological analysis and comparison with Simplisphinctes s. str. and S. (Paralytohoplites). Furthermore, our results allow a refinement of the chronostratigraphic position of the Chitnoidella boneti-Subzone in Europe and place the zone in the lowermost Upper Tithonian. Another important fossil group for global correlations at the Middle/ Upper Tithonian boundary are radiolarians; in Argentina, radiolarians indicating the youngest radiolarian association with Vallupus hopsoni and representing the Zone 4, upper Subzone 4 beta of Pessagno have been found in the Windhauseniceras internispinosum Zone. Calcareous nannofossils and dinoflagellates can also deliver useful data. The differing stratigraphic calibration potentials of these fossil groups are discussed. © 2008 Gebrüder Borntraeger.